Planning Egypt's new settlements : the politics of spatial inequities = Takhṭīṭ al-mudun al-jadīdah fī Miṣr : siyāsāt al-tabāyun al-makānī - Wahdan, Dalia (Cairo Papers in Social Science, 2013)
This study critically analyzes the paradigms and practices of planning in Egypt since 1952. It interrogates the politics of national and physical planning while tracing the ideas that informed the establishment of new settlements in the country across the regimes of Nasser, Sadat, and Mubarak. Based on primary and secondary data, the study argues that under Nasser, plans often diverged from their blueprints and revealed the myth of 'technical objectivity' that underpinned the planning industry. It outlines the program of new settlements under Sadat and unveils the systematic exclusion of planners from decision-making apparatuses while institutionalizing 'profit-opportunism' in favor of private interests. The study then demonstrates the decline of planning under Mubarak and its emergence into a 'special purpose vehicle' in service of real estate developments associated with neoliberal shifts of the economy and skewed toward resource and privilege concentration in the hands of a few, thus further exacerbating uneven spatial morphologies.